2016
DOI: 10.1080/02687038.2016.1148902
|View full text |Cite
|
Sign up to set email alerts
|

The effect of syntactic frequency on sentence comprehension in standard Indonesian Broca’s aphasia

Abstract: Background: Comprehension of reversible sentences that have derived word order has often been reported as impaired in agrammatic aphasia. Most accounts of this phenomenon refer to the syntactic differences between derived and base word order of the arguments. However, it has been demonstrated that in agrammatic spontaneous speech in standard Indonesian (SI) passives are produced at a rate that is proportional to that of healthy speakers. The main difference between passives in SI and in other languages is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…As per the group results, we did not find a significant difference between the production performance of active and passive sentences in SI agrammatic speakers. Similar results were found in the comprehension study by Jap et al (2016), where passive structures were found to be preserved. However, further scrutiny reveals that the scores for the non-canonical condition are quite diverse across subjects.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As per the group results, we did not find a significant difference between the production performance of active and passive sentences in SI agrammatic speakers. Similar results were found in the comprehension study by Jap et al (2016), where passive structures were found to be preserved. However, further scrutiny reveals that the scores for the non-canonical condition are quite diverse across subjects.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, the study by Jap et al (2016) suggested that the preservation of the passive structure in SI aphasic comprehension is at least partially caused by the frequent occurrence of the structure in the language.…”
Section: Frequency In Aphasic Sentence Processingmentioning
confidence: 98%
“…There are only few studies on Indonesian aphasic speakers in general and only some of those used the Token Test in their studies (e.g. Anjarningsih et al, 2012;Jap et al, 2016). As such, future research with the tool could not only improve its sensitivity via norm establishment, but also test its validity in the context of other language and cognitive tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from its uses in the present study, the adaptation of the Token Test can contribute further in both research and clinical contexts of Indonesian aphasiology. One such instance where this present norm data was used, was in a study of sentence comprehension in Broca's aphasic speakers in Indonesian (Jap, Martinez-Ferreiro, & Bastiaanse, 2016). After attaining norms on healthy participants and individuals with aphasia, the Token Test in Indonesian can be used, if needed, to compare scores crosslinguistically with many standardized aphasia batteries like the Aachen Aphasia Test (original Dutch version by Graetz, De Bleser, & Willmes, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…((reads aloud)) once upon a time there was a little boy. Alisia asks her peers if they still know what their schoolmaster and Mary once told and acted out, concerning the real story about the little pole (lines [183][184][185][186][187][188]. The turn-initial 5 placement of 'you know' serves as a projection for displaying agreement by the other participants, with her statement that they won't be following the suggestion of the attic, since that does not agree with the real (original) story (line 190).…”
Section: Indicating Shared Knowledge With Other Participantsmentioning
confidence: 99%